ADMINSTRATIVE POLICY IMMIGRATION AND THE URGENCY OF IMPLEMENTATION IN INDONESIA - Olyvia Sindiawaty; Maidah Purwanti (Journal of Law and Border Protection, 2020)
Immigration Administrative Policy or commonly known as TAK, is a right that can be carried out by the immigration authorities in providing an action on a problem faced in order to maintain the sovereignty of the Unitary Republic of Indonesia. The existence of this action certainly gives the authority to deal with the State of Foreign Affairs (WNA) which is quite extensive but aimed at the same results, namely deportation or ending in jail. It is undeniable, that there are still many important points in Law No. 6 of 2011 which still need a lot of explanation, as well as leading to the Immigration Adminstrative Act. The process of investigating perpetrators of violations of the Immigration Act is carried out based on the provisions in the Criminal Procedure Code as a lex generalis and the Immigration Act as a lex specialis. In carrying out immigration law enforcement functions, there are still constraints faced by PPNS. Immigration includes lack of knowledge, lack of operational funds, lack of community participation in reporting the presence of foreigners in their environment, weak coordination with other legal apparatuses and obstacles originating from legal factors that are still taken lightly . It is hoped that the writing of this paper will awaken various parties who still view the immigration law as one eye, because immigration is an important thing for a country to maintain the country's sovereignty. Legal services through a variety of actions, one of which is the Immigration Administration.